Early Diagnosis of Pathological Changes in Visual System of Prolactinoma Patients Using Visual Evoked Potential - Keramti, Shahrzad; Ojani, Fatemeh; Shushtarian, Seyed Mohammad Masoud; Shojaei, Ahmad; Mohammad-Rabei, Hossein (Journal of Ophthalmology and Research, 2021)
Aim Prolactinoma is the most Pituitary adenomas that affect young women at fertile age. Visual impairment is a common presentation of this condition. Visual pathway mainly optic nerve may be affected in these patients. Visual evoked potential is one of the techniques to screen the visual pathway. The aim of the present work is to search for the probable adverse effect of Prolactinoma on visual pathway using visual evoked Potentials. Patients and Method Fifteen female patients with an age range of 20-40 years were selected. The patients had a healthy visual system as far as visual acuity, field of vision & magnetic resonance imaging of the brain was concerned. The latency and amplitude of visual evoked potential, P100 peak was recorded for this patients & 15 age and sex matched controls with the healthy visual system. Results The mean age was 29.4±6.68 and 29.13±6.82 is case and control group respectively. The mean visual acuity in case was 0.00±0.00 (Log MAR) and 0.00±0.00 (Log MAR) in control group. The difference in values were not statistically significant as for as age (P=0.967) and visual acuity (P=1) was concerned. The values obtained for latencies were 101.13 ±5.95 and 98.06 ±4.01 for case and control groups respectively. In case of amplitude the values were 8 ±1.96 and 7.93 ±2.06 in case and control groups. The values for visual evoked potential were statistically significant for latency between case and control groups (P=0.036), where as in case of amplitude the difference between two groups i.e., case and control groups were not significant (P=0.756) Conclusion Prolactinoma might have adverse effect on visual pathway mainly optic nerve despite normal visual acuity, field of vision and brain magnetic resonance imaging which can be diagnosed by latency of pattern visual evoke